Read My Lips: Reading English Application Tool In The Development Of Middle Youth Students Thru Language Instruction Using Phonetic Sounds - Sanqui, Rommel; E. Sanqui, Roselyn; C. Valera, Davidson (International Journal of Educational Research & Social Sciences, 2022)
Reading is a key to learning skills. It enhances our learning skills. It develops comprehensions opens up a lot of answers for further learning. And the use of computer programs and applications supplements regular reading instructions. The computer application for Project R.E.A.D. M.Y. L.I.P.S (Reading English Application tool in the Development of Middle Youth students thru Language Instruction using Phonetic Sounds), is a computer based program, which provides the compilation of options such as: Phonetic Alphabet, Let’s Read and Let’s Play options. The system is designed to provide pre elementary English Teacher with a supplementary tool in teaching reading. The system operates on different types of computer specification. The screen resolution must be 14 inches as minimum requirements to make it easy and compatible to use. A minimum storage space is 256 MB. Installation package and executable file were made for good and easy installation and operation of the system. The system was evaluated excellent in its performance and functionality using the ISO evaluation tool for software developemnt.